Constitutional Rights as Bribes - Dixon, Rosalind (2019)
Constitutions worldwide protect an increasingly long list of rights. Constitutional scholars point to a variety of top-down and bottom-up explanations for this pattern of rights expansion. This article, however, identifies an additional, under-explored dynamic underpinning this pattern in certain countries—i.e. the pairing of constitutional rights with various forms of structural constitutional change, as part of a trade between civil society and dominant political actors in their aspirations, or support, for constitutional change. This form of trade, the article further suggests, has potential troubling consequences for democracy: it can pave the way for the consolidation of dominant party or presidential rule in ways that limit the -term effectiveness of rights-based constitutional changes themselves, and pose a major threat to the institutional “minimum core” necessary for a true democracy. This, the article argues, suggests a greater need for caution on the part of civil society before accepting rights as a form of ‘bribe’, or inducement, to support certain forms of structural constitutional change. For democratic constitutional designers, it also points to the advantages of ‘unbundling’ different forms of constitutional change. The article explores these arguments by reference to two recent examples of constitutional change, in Ecuador and Fiji, involving the combination of rights-based change with increasingly non-competitive forms of democratic rule.